Mandarin need analysis in East Coast Region of Malaysia - Yong, Ying Mei; Cheng, Ching Yee (2016)
Malaysia and China cooperated to build up Malaysia-China Kuantan Industrial Park (MCKIP) and China-Malaysia Qinzhou Industrial Park at Kuantan, Pahang. Both of parks will create a lot of business and employment opportunities in East Coast Region of Malaysia. Those are mastering in Mandarin may increase the cooperation in international trade and economy between Malaysia and China. Therefore, Mandarin learners from East Coast Region of Malaysia will be increase as might be expected. Thus this study investigated Mandarin need analysis in East Coast Region of Malaysia through interview and questionnaire. The finding shows that the market requirement of Mandarin courses are Business Mandarin and Mandarin for travelling in East Coast Region of Malaysia. The investment of China in Pahang by One Belt One Road economy policy of China may prompt the demand of Mandarin courses. As a Mandarin Language and Culture Centre (MLCC), Universiti Malaysia Pahang played an active role in providing the Mandarin courses to the residents in East Coast Region of Malaysia. It’s will enhance the friendship and international relations between Malaysia and China.